2016
DOI: 10.1523/jneurosci.3660-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rivalry-Like Neural Activity in Primary Visual Cortex in Anesthetized Monkeys

Abstract: Two incongruent images viewed by the two eyes cause binocular rivalry, during which observers perceive continuous alternations between these two visual images. Previous studies in both humans and monkeys have shown that the primary visual cortex (V1) plays a critical role in the rivalry perception. However, it is unclear whether the rivalry activity observed in V1 relies on conscious influences. Here, we examine the responses of V1 in monkeys under general anesthesia. With intrinsic signal optical imaging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…1 So, while a neural marker of perceptual switches persists under inattention conditions in V1, diverting attention seemingly changes how later visual areas respond to BR stimulation. The notion of a preserved marker of switches in V1 is consistent with recent optical imaging work in monkeys, showing that an alternating pattern of V1 activity in response to rivalry stimulation remains even under general anesthesia (Xu et al, 2016). In potentially related work, Roeber, Veser, Schröger, & O'Shea, 2011 measured event-related potentials (ERPs) and discovered a difference in response to rivalrous stimuli compared to non-rivalrous stimuli; a difference that remained even if the stimuli were unattended (also see Katyal, Engel, He, & He, 2016).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…1 So, while a neural marker of perceptual switches persists under inattention conditions in V1, diverting attention seemingly changes how later visual areas respond to BR stimulation. The notion of a preserved marker of switches in V1 is consistent with recent optical imaging work in monkeys, showing that an alternating pattern of V1 activity in response to rivalry stimulation remains even under general anesthesia (Xu et al, 2016). In potentially related work, Roeber, Veser, Schröger, & O'Shea, 2011 measured event-related potentials (ERPs) and discovered a difference in response to rivalrous stimuli compared to non-rivalrous stimuli; a difference that remained even if the stimuli were unattended (also see Katyal, Engel, He, & He, 2016).…”
Section: Introductionsupporting
confidence: 86%
“…Interestingly, fMRI studies have also failed to find a neural correlate of perceptual suppression during unattended flash suppression (Moradi & Heeger, 2009) or its more potent analog continuous flash suppression (Watanabe et al, 2011). In fact, the latter study demonstrated that withdrawal of attention, but not addition of a suppressor prompted a reduction in V1 BOLD activity (but see Yuval-Greenberg & Heeger, 2013 and Xu et al, 2016). …”
Section: Introductionmentioning
confidence: 90%
“…Although that is an interesting study, given that each eye's stimulus was at threshold level and often visible, this result by itself could not be taken as clear demonstration of rivalry without awareness. Studies in anesthetized monkeys also showed neural evidence for rivalrylike competition in monkey V1 (4,21). However, along with the differences between species, there are also important differences between the alert but unaware of the stimulus feature and being in a state of anesthesia; thus, it is difficult to generalize the results from the anesthetized monkeys to alert human observers.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic signal optical imaging Chronic optical/recording chambers were implanted as described previously (Li et al, 2013;Xu et al, 2016). The only difference is that we used silicon artificial dura instead of tecoflax dura to allow electrode penetration (Arieli et al, 2002).…”
Section: Methods Detailsmentioning
confidence: 99%